PENGARUH CSR TERHADAP NILAI PERUSAHAAN: INTEGRASI MANAJEMEN LABA SEBAGAI MEDIASI DAN KEPEMILIKAN KELUARGA SEBAGAI MODERASI - Stacia Senjaya; Fransiskus Randa; Ferdinandus Sampe (Jurnal Magister Akuntansi Trisakti, 2021)
The purpose of this study is to investigate the role of family ownership integration in moderating and earnings management in mediating the relationship between CSR and firm value. The population used is all companies listed on the Indonesia Stock Exchange (BEI) with the 2015-2018 research period. The number of samples is 67 companies each year, which were selected by purposive sampling method. This study uses documentary data, namely annual reports and financial reports. Path analysis is used to analyze data. The results of this study indicate that CSR has a significant positive effect on earnings management, also earnings management on firm value has a significant positive relationship. The family ownership variable in moderates the relationship between CSR and earnings management is type Pure Moderation, conversely earnings management in mediating the relationship between CSR to the firm's value is type of No Mediation, nor is there any effect of integration of family ownership and earnings management on the relationship of CSR and firm value. The implication of this research, especially for family firms to maintain control of the company's operations, especially in the socio-emotional aspect compared to the financial aspect, because this contributes stakeholder to avoid the impact of earning management practices with the higher the discretionary accrual value is indicated to hide actions that harm firm’s reputation.